1987
DOI: 10.1007/bf01821085
|View full text |Cite
|
Sign up to set email alerts
|

Neotectonic evolution of northwestern-continental Greece

Abstract: ZusammenfassungSp~itmioz~ine Sedimentationsprozesse sowie strukturelle Entwicklung ~ndern sich in NW kontinental-Griechenland in E-W Richtung.An der Ionischen Kiiste wurden w~hrend der sp~tmio-z~inen Absenkung des Sedimentationsraumes m~chtige Olisthostrome und intrafoliale Falten gebildet. An der Grenze des Plio/Pleistoz~s wurden flache Uberschiebungen, L6sungsschieferung und NNW bis NNE streichende, ge6ffnete Falten entwickelt. Diese tektonische Strukturen sind das Ergebnis aktiver Plattenkonvergenz zwischen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0
12

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 25 publications
0
40
0
12
Order By: Relevance
“…The main tectonic feature in the area is the Trichonis lake fault that bounds the graben to the south and forms a distinct topographic escarpment (Doutsos , 1987). Nevertheless this fault didn't rapture during the earthquake sequence under study, as suggested by Evangelidis, 2008 andKiratzi et al, 2008.…”
Section: Geological -Tectonic Settingmentioning
confidence: 97%
See 1 more Smart Citation
“…The main tectonic feature in the area is the Trichonis lake fault that bounds the graben to the south and forms a distinct topographic escarpment (Doutsos , 1987). Nevertheless this fault didn't rapture during the earthquake sequence under study, as suggested by Evangelidis, 2008 andKiratzi et al, 2008.…”
Section: Geological -Tectonic Settingmentioning
confidence: 97%
“…The broader area of Trichonis lake is an active graben (Doutsos , 1987) with WNW-ESE strike and a length of about 30km (Fig.1). It is formed almost perpendicular to the Hellenides fold and thrust structures and is bounded by large normal faults.…”
Section: Geological -Tectonic Settingmentioning
confidence: 99%
“…The Patraikos Gulf located on the northwestern part of Peloponnese, lies approximately 100 km east of the Hellenic trench, immediately behind the Plioquaternary fold belt, which runs parallel to the coast of western Greece (Doutsos et al, 1987). The mountains of Klokova and Varasova are located to the northeast of the Gulf, consisted of Cretaceous limestones and Eocene flysch (Gavrovo zone).…”
Section: Geographical and Geological Settingmentioning
confidence: 99%
“…From a tectonic point of view, Patraikos Gulf area consists the western part of a major East/West graben system, behind the Plioquaternary fold belt (Doutsos et al, 1987). This graben system extends from the boundary of a marginal compressional zone (Brooks and Ferentinos, 1984) associated with the subducting Western Hellenic arc, to the center of the Aegean Sea (Figure 2).…”
Section: Geographical and Geological Settingmentioning
confidence: 99%
“…Studies of the focal mechanisms from earthquakes within the area, have shown that the tectonic regime of the area varies from thrust and strike slip to normal (Mercier et al, 1972;King et al, 1983;Doutsos et al, 1987;Underhill, 1989;Waters, 1994;Hatzfeld et al, 1995).…”
Section: Introductionmentioning
confidence: 99%